Contribution of Fetal MR Imaging in the Prenatal Diagnosis of Zellweger Syndrome - Mochel, F.; Grébille, A.-G.; Benachi, A.; Martinovic, J.; Razavi, F.; Rabier, D.; Simon, I.; Boddaert, N.; Brunelle, F.; Sonigo, P. (American Journal of Neuroradiology, 2006)
Summary: Zellweger syndrome (ZS), or cerebrohepatorenal syndrome, was the first described peroxisomal biogenesis disorder. It represents the most severe phenotype, and some of its multiple congenital anomalies can manifest prenatally. Fetal hypokinesia, renal hyperechogenicity, and cerebral ventricular enlargement are the most common reported fetal features. Single and/or late detectable manifestations account for most of the difficulties of prenatal diagnosis, as well as the limitations of ultrasonography itself. Prenatal diagnosis, however, can be achieved through (1) assays of concentrations of peroxisomal metabolites (very-long-chain fatty acids, bile acids, intermediates, plasmalogens), (2) activities of peroxisomal enzymes (dihydroacetone-phosphate acyltransferase), or (3) molecular screening techniques, if available. We report on the contribution of MR imaging to the diagnosis of ZS in 2 unrelated fetuses. MR imaging was performed in the third trimester because of cerebral ventricular enlargement diagnosed on routine sonography examinations. In both cases, MR imaging revealed ZS-characteristic abnormal cortical gyral patterns, impaired myelination, and cerebral periventricular pseudocysts. In addition, MR imaging revealed renal microcysts and hepatosplenomegaly in one case. The high level of resolution of MR imaging, which allows analysis of cerebral gyration and myelination, facilitates the prenatal diagnosis of complex polymalformative syndromes such as ZS.